2021
DOI: 10.3390/vaccines9030266
|View full text |Cite
|
Sign up to set email alerts
|

Escherichia coli Heat-Labile Enterotoxin B Subunit Combined with Ginsenoside Rg1 as an Intranasal Adjuvant Triggers Type I Interferon Signaling Pathway and Enhances Adaptive Immune Responses to an Inactivated PRRSV Vaccine in ICR Mice

Abstract: Porcine reproductive and respiratory syndrome virus (PRRSV) is a major pathogen that has threatened the global swine industry for almost 30 years. Because current vaccines do not provide complete protection, exploration of new preventive strategies is urgently needed. Here, we combined a heat-labile enterotoxin B subunit of Escherichia coli (LTB) and ginsenoside Rg1 to form an intranasal adjuvant and evaluated its enhancement of immune responses in mice when added to an inactivated-PRRSV vaccine. The combinati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 63 publications
0
8
0
Order By: Relevance
“…Consistent with our results, previous studies showed that DDA is capable of producing high levels of IFN-γ in CD4 + CD8 − lymphocytes 54 , 55 . Additionally, LTB could potentially induce the production of IFN-γ in both CD4 + CD8 − and CD4 − CD8 + lymphocytes 56 . Mechanisms involving LTB and DDA and lymphocyte stimulation are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent with our results, previous studies showed that DDA is capable of producing high levels of IFN-γ in CD4 + CD8 − lymphocytes 54 , 55 . Additionally, LTB could potentially induce the production of IFN-γ in both CD4 + CD8 − and CD4 − CD8 + lymphocytes 56 . Mechanisms involving LTB and DDA and lymphocyte stimulation are not well understood.…”
Section: Discussionmentioning
confidence: 99%
“…This study indicates that the E515-adjuvanted Bb vaccine activates Th1/Th2/Th17 cell responses. Recently, a virus vaccine containing GS adjuvant was found to evoke balanced Th1/Th2/Th17 responses in a mouse model [ 41 ]; thus, the role of GS in the effects of the E515 adjuvant is worthy of further exploration.…”
Section: Discussionmentioning
confidence: 99%
“…Our antibody results demonstrated that the ability of GSLS-NPs to improve antibody responses was not dose dependent, and the optimal GSLS-NPs dose for adjuvant activities appeared to be 5 mg/kg, which elicited a stronger serum IgG antibody response, specifically responses involving the IgG1 and IgG2a isotypes, 14 days after a booster immunization than vaccination alone. The predominant IgG subclass changes progressively during an immune response, which is dependent on the pattern of cytokines secreted by CD4 + T cells [14]. In mice, IL-10 favours IgG1 isotype (Th2 type) production by activated B cells, while IFN-γ promotes IgG2a production (Th1 type).…”
Section: Discussionmentioning
confidence: 99%
“…IgA + cells were identified with an immunohistochemical staining method described previously [14]. Briefly, fixed intestinal samples were embedded in paraffin, sectioned at a thickness of 6 µm, and mounted onto glass slides.…”
Section: Immunohistochemistry and Haematoxylin-eosin Stainingmentioning
confidence: 99%